One-step synthesis of nitrogen-doped graphene powders and application of them as high-performance symmetrical coin cell supercapacitors in different aqueous electrolyte - Arvas, Melih Besir; Karatepe, Nilgun; Gencten, Metin; Sahin, Yucel (WILEY, 2022)
In this study, symmetric supercapacitors in the form of coin cells were produced by using N-doped graphene powders as electrode components. Nitrogen-doped graphene powders were prepared by Yucel's Method with cyclic voltammetry at different potential ranges for selective modification of the powders with functional groups. Electrochemical, spectroscopic, and microscopic characterizations of N-doped graphene powders were carried out. The formation of graphene layers was supported by scanning electron microscopy and Raman analysis. Functional groups formed on the surfaces of N-doped graphene powders were determined by X-ray photoelectron spectroscopy. Specific capacitances of symmetric supercapacitors prepared with N-doped graphene powders were determined by cyclic charge-discharge tests. The highest specific capacitance, energy and power values were determined as 235.3 F.g(-1), 158.2 Wh.kg(-1) and 1760 W.kg(-1), respectively.
Keywords: 2D materials; cyclic voltammetry; N-doped graphene powders; supercapacitor; Yucel's method; PENCIL GRAPHITE-ELECTRODES; OXYGEN REDUCTION REACTION; DOUBLE-LAYER CAPACITANCE; ELECTROCHEMICAL PERFORMANCE; EFFICIENT ELECTROCATALYST; HYBRID SUPERCAPACITORS; POTENTIAL APPLICATION; POROUS CARBON; PARTICLE-SIZE; Energy & Fuels; Nuclear Science & Technology